2008
DOI: 10.1007/bf03086124
|View full text |Cite
|
Sign up to set email alerts
|

Cell transplantation for cardiac regeneration: where do we stand?

Abstract: During the last decade transplantation of cells into the heart has emerged as a novel therapy for the prevention and treatment of heart failure. Although various cell types have been used, most experience has been obtained with the progenitor cells of skeletal muscle, also called myoblasts, and a wide array of bone marrow-derived cell types. The first preclinical studies demonstrated an improvement in global and regional heart function that was attributed mainly to a direct contractile effect of the transplant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 69 publications
0
6
0
Order By: Relevance
“…Cell transplantation therapies for organ function restoration and tissue regeneration have been developed utilizing adult cells, adult stem cells, and iPSCs [159][160][161][162]. Similar to organ transplantation, adult cell transplantation has been used to substitute for a lack of native organ function.…”
Section: Cell Transplantationmentioning
confidence: 99%
See 2 more Smart Citations
“…Cell transplantation therapies for organ function restoration and tissue regeneration have been developed utilizing adult cells, adult stem cells, and iPSCs [159][160][161][162]. Similar to organ transplantation, adult cell transplantation has been used to substitute for a lack of native organ function.…”
Section: Cell Transplantationmentioning
confidence: 99%
“…Recognizing what part or parts of an organ are most vital to its function, such as the islet cells for the pancreas, are critical for engineering functional whole organs. Adult stem cells and iPSCs have both been used to regenerate cells and damaged tissue via injection [160,161]. Stem cells are transplanted with the intention of using the microenvironmental cues of the surrounding tissue to induce differentiation of the stem cells into the same type of cell as the tissue they are injected in [164].…”
Section: Cell Transplantationmentioning
confidence: 99%
See 1 more Smart Citation
“…inducing angiogenesis, inhibiting apoptosis, and enhancing scar tissue formation, or possibly by myocardial regeneration. 5,6 BMMC therapy: from experimental studies to clinical trials In 2001, Orlic et al reported that subsets of BMMCs are capable of replacing infarcted myocardium and improve ventricular function after AMI in mice. 7 Moreover, a study by Quaini et al, investigating sex-mismatched transplanted hearts, demonstrated migration of cells from the recipient to the donor heart.…”
Section: Introductionmentioning
confidence: 99%
“…Subsequent studies have mainly used bone marrow (BM)-derived cells, either the whole mononuclear fraction or selected cell sub-populations. 3 The overall impression is that most clinical studies, some of which include large numbers of controls, have reported benefits to patients, often with a significant long-term improvement of their clinical state. 4 …”
mentioning
confidence: 99%